Impacto del TLC Perú – China en las exportaciones peruanas de harina de pescado a China durante el 2004 al 2016 - Flores Rodriguez, José Fernando (2020)
The main objective of this research is to evaluate the impact of the Peru – China Free Trade Agreement (FTA) on peruvian fishmeal exports, although all FTAs seek to strengthen trade flows between two countries – or a set of them – not necessarily both parties share the benefits equally. The research also focuses on studying six years before and after the FTA was signed (FTA was effective since March 2010) which will allow us to draw conclusions based on two “different” scenarios. Perú is the main exporter of fishmeal in the world and has as its potential demand the chinese market; however, one issue should be highlighted. Can the FTA generate a negative impact on peruvian fishmeal exports after the signing of the agreement? To answer that question, we must apply and understand the economic theory behind, the concepts of international trade ans characteristics of demand. Also it is important to study and measure the immersed variables that may be the cause of the phenomenon such as international prices, GDP, terms of trade, inflation and real exchange rate that will serve as key tools at the moment of assess the impact of the FTA through an econometric model. Finally, international trade theory explains that FTA will energize all sectors of the economy of both countries. However, this research shows that the phenomenon does not apply in the case of Peruvian exports of fishmeal to China. It is necessary to go further.